Clarivein® mechano-chemical ablation an interim analysis of a randomized controlled trial dose-finding study. (April 2016) - Lam, YL; Toonder, Irwin M; Wittens, Cees HA
Objectives: The ClariVein® system is an endovenous technique that uses mechano-chemical ablation to treat incompetent truncal veins. This study was conducted to identify the ideal Polidocanol dosage and form for mechano-chemical ablation in order to occlude the great saphenous vein. When adhering to safe dosage levels, sclerosants with higher concentrations potentially limit the extent of treatment. It has been demonstrated that this problem may be overcome by using Polidocanol as a microfoam. This paper was established on findings of a preliminary analysis. Material and methods: The initial study was a single-blinded multicenter randomized controlled trial where patients are allocated to three treatment arms. Group 1 consisted of mechano-chemical ablation +2% Polidocanol liquid, group 2: mechano-chemical ablation +3% Polidocanol liquid and group 3: mechano-chemical ablation +1% Polidocanol foam Results: Eighty-seven, 34 males and 53 females (60.9%), mean age 55 years s.d. 16.0 (range 24–84), were enrolled in the study. Treatment length was 30 cm (range 10–30) for 95.2% of the patients. Mean operating time was 16 minutes (range 5–70). The mean saphenofemoral junction diameter (7.7 mm) was similar in all three groups. At 6 weeks post-treatment duplex ultrasound showed that 25 out of 25 = 100%, 27 out of 28 = 96.4% and 13 out of 23 = 56.5% were occluded in the mechano-chemical ablation + 2% Polidocanol liquid, mechano-chemical ablation + 3% Polidocanol liquid and mechano-chemical ablation + 1% Polidocanol microfoam respectively ( p  < 0.001). However, stricter scrutiny showed that the anatomical success rate defined as occlusion of at least 85% of the treated length to be 88.0%, 85.7% and 30.4% respectively ( p  < 0.001). Conclusion: Mechano-chemical ablation using ClariVein® combined with 1% Polidocanol microfoam is significantly less effective and should not be considered as a treatment option of incompetent truncal veins. Further investigation to determine the ideal Polidocanol liquid dosage with mechano-chemical ablation is advocated and is being conducted accordingly.